Experimental investigation of bond characteristics between CFRP and steel under tensile loads - Kalavagunta S.; Naganathan S.; Bin Mustapha K.N.; Rezaii A.S. (Jordan University of Science and Technology, 2023)
Bond length; Bond strength (chemical); Bonding; Carbon; Carbon fiber reinforced plastics; Debonding; Fiber reinforced plastics; Bond characteristics; Carbon fiber reinforced polymer; Cold-formed steel; Damaged infrastructure; Experimental investigations; In-depth understanding; Strengthening methods; Surface preparation technology; Strengthening (metal)